Modeling and experimental validation of a transient direct expansion geothermal heat exchanger. (September 2015) - Rousseau, Clément; Comlan Fannou, Jean-Louis; Lamarche, Louis; Ouzzane, Mohamed; Kajl, Stanislaw
Highlights: We developed a model of a ground exchanger in a DX geothermal heat pump. We validated this model experimentally. We analyzed the impact of different parameters of the borehole on the heat flux rate. Abstract: Geothermal heat pump technology is currently one of the most interesting technologies used to heat buildings. There are two designs used in the industry: geothermal heat pump using a secondary ground loop and direct expansion (DX) ground source heat pump. The latter is less used, with one of the possibly reasons being that less research has carried out into the design of this sort of heat pump. In this paper, a model of a ground heat exchanger of a DX geothermal heat pump is presented in heating mode and a comparison with experimental results is presented. It is shown that the model is adequately validated by our experiment. After this validation, an analysis of the effect of the mass flow rate, the length and the angle of the borehole on the heat flux rate is presented. To conclude, an optimum configuration for the experiment is proposed.